Osteoporosis Improved by Romosozumab Therapy in a Patient With Type I Osteogenesis Imperfecta - Antara Dattagupta, MD, MEng; Steven Petak, MD, JD (AACE Clinical Case Reports, 2023)
Background/Objective: Osteogenesis imperfecta (OI) is a genetic disorder that affects type 1 collagen synthesis causing increased bone fragility, low bone mass, and skeletal deformity. Bisphosphonates are recommended for treatment of OI patients; however, the efficacy of sclerostin inhibitors such as romosozumab has not been determined in OI patients with osteoporosis. Case Report: A 52-year-old G2P2 clinically diagnosed with OI, with a history of multiple fractures beginning in childhood presented with low bone mass. On physical examination, blue sclera was observed. She was previously treated with alendronate therapy from April 2014 to June 2015 without significant improvement in bone mineral density (BMD). After the onset of menopause, she began romosozumab 210 mg subcutaneous therapy once a month for 12 months. Repeat dual-energy X-ray absorptiometry showed an increase of 10.3% in BMD of the spine and a 5.4% increase in BMD of the right hip. The trabecular bone score increased by 5.2%. Discussion: Current literature is limited regarding the use of sclerostin inhibitors in OI patients. Our patient’s improvement in BMD of the spine and right hip after romosozumab therapy was significant at a 95% confidence level, compared to treatment initiation. Her trabecular bone score also improved significantly. Six months into our patient’s treatment course, a case in Japan of a male with severe osteoporotic OI and recurrent fractures showed improvement in BMD after romosozumab therapy. Conclusion: This case highlights our patient’s significant response to romosozumab and warrants further investigation of romosozumab as a potential treatment option for OI patients with osteoporosis.